From Theory to Practice: A Qualitative Scoping Review on Nurses' Barriers in Implementing Evidence-Based Practice in Hospitals - Yodha Pranata; Athaya Zafira Yuflih; Rizky Lukman Saputra; Ajani Mutiarasani; Yutika Wiguna; Tita Hartati (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Evidence-based practice (EBP) is essential for improving healthcare quality and clinical outcomes. However, nurses face significant barriers to implementing EBP in hospital settings, ranging from individual knowledge gaps to systemic challenges. Addressing these barriers is crucial for bridging the gap between research and practice. This scoping review aims to identify and synthesize qualitative evidence on the barriers nurses face in implementing EBP in hospitals and to provide actionable insights to guide policy and practice improvements. A qualitative scoping review was conducted using a systematic search strategy across four databases (Scopus, PubMed, EBSCOhost) based on the PCC framework. Articles were included if they employed a qualitative design, focused on nurses' experiences with EBP, and were available in full text. Nine articles meeting the inclusion criteria were analyzed thematically using the Braun and Clarke approach. Thematic analysis revealed key barriers to EBP implementation: Lack of Institutional and Managerial Support, Time Constraints in Implementing EBP, Lack of Access to Resources and Information, Knowledge and Training Gaps in EBP, Tradition-Based and Intuition-Based Practice Culture in EBP, Low Motivation and Self-Confidence in Implementing EBP, and Barriers in Language and Understanding of Scientific Evidence.  Overcoming barriers to EBP in nursing practice demands a multifaceted approach that combines policy support, resource allocation, and capacity building. These strategies are vital for fostering a culture of evidence-based care in hospital settings. Keywords: Evidence-Based Practice (EBP), EBP Implementation, Nursing Barriers, Healthcare Implementation